The prospects of LNG in Singapore - Liu, Joo Lin (2015)
The phenomenon of global warming has become more apparent with higher global temperatures as contributed by increased levels of greenhouse gases. Hence, the world has become more concerned about the environment. For the maritime industry, shipping companies are actively looking into alternatives to promote green shipping including the adoption of Liquefied Natural Gas (LNG) as an alternative. LNG is widely discussed owning to its properties of low carbon combustion and almost zero sulphur emission. In addition, the new stringent regulations to lower sulphur emission globally, it becomes a major concern for shipping companies to consider the switch to cleaner alternatives. Meanwhile, the pilot LNG bunkering programme initiated by Maritime and Port Authority of Singapore aims to transform Singapore into one of the LNG bunkering location by 2020. However, there are several factors to consider prior to building a LNG bunkering terminal. The designs of LNG fuelled vessels deviate from those conventional ships due to the placement of the storage tanks according to the size of the vessels. It also has to comply with IMO regulations to ensure safety and minimize the risk on board while carrying liquid gases in bulk. Furthermore, the dual fuel engine used in LNG fuelled vessels need to be evaluated for its suitability before mounting onto the vessels as the cost of conversion is high and may take years to achieve the return on investment. Singapore LNG Corporation was set up as a receiving storage and regasification terminal. However, it lacks the necessary infrastructures and facilities required for a bunkering terminal. The different options of loading the fuel to the vessels and the associated equipment are important for Singapore LNG Corporation to consider. Singapore is now a step ahead to develop as a LNG bunkering terminal due to its existing LNG terminal. The initiatives and programmes are strongly supported by the government and authorities of Singapore which aid in the development of a regional hub for LNG bunkering. This research paper has found that the prospect of LNG in Singapore is positive given its technical expertise and knowledge supported by the government bodies and the maritime industry in Singapore.